Immuno-Chromatographic Test System Application for Rapid Detection of Francisella tularensis Lipopolysaccharide in Monitoring of Natural Foci - A. A. Zaitsev; O. A. Gnusareva; N. S. Tsareva; V. V. Ostapovich; I. Yu. Borzdova; A. N. Kulichenko (Проблемы особо опасных инфекций, 2013)
Immuno-chromatographic test systems are shown to be applicable for rapid detection of tularemia microbe lipopolysaccharide for identification of Francisella tularensis strains isolated in natural foci, and in epizootiologic survey – for the analysis of suspensions of ixodic ticks and internal organs of dead animals.